2019
DOI: 10.1007/s11916-019-0739-3
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Behavioral Therapy for Migraine: Knowledge to Date, Mechanisms for Assessing Adherence, and Methods for Improving Adherence

Abstract: Purpose of Review In other disease states, adherence to behavioral therapies has gained attention, with a greater amount of studies discussing, defining, and optimizing adherence. For example, a meta-analysis formally discussed adherence in 25 studies of CBT for 11 different disorders, with only 6 of the 25 omitting addressing or defining adherence. Many studies have discussed the use of text messages, graph-based adherence rates, and email/telephone reminders to improve adherence. This paper examined the avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
(51 reference statements)
1
13
0
Order By: Relevance
“…Interestingly, in two of the studies, MI pre-treatment did facilitate an increase in informal help seeking from parents and significant others. 37 Patients may want to engage in behavioral therapy but for reasons presented in this study (and similar previously published reasons) [see several of the recent reviews on this topic 3,38 ], there are too many other barriers, oftentimes external factors, preventing them from doing so. 3 Factors such as time and cost were themes across both the MI and TAU groups and likely account for the discrepancy between initiating behavioral therapy in the MI group and attending the session.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Interestingly, in two of the studies, MI pre-treatment did facilitate an increase in informal help seeking from parents and significant others. 37 Patients may want to engage in behavioral therapy but for reasons presented in this study (and similar previously published reasons) [see several of the recent reviews on this topic 3,38 ], there are too many other barriers, oftentimes external factors, preventing them from doing so. 3 Factors such as time and cost were themes across both the MI and TAU groups and likely account for the discrepancy between initiating behavioral therapy in the MI group and attending the session.…”
Section: Discussionmentioning
confidence: 70%
“…36 MI sessions as short as 15 minutes in length, performed as pretreatment, improved attendance for mental health treatment, and thus an increased uptake of mental health interventions. 37 Patients may want to engage in behavioral therapy but for reasons presented in this study (and similar previously published reasons) [see several of the recent reviews on this topic 3,38 ], there are too many other barriers, oftentimes external factors, preventing them from doing so. However, MI did not change the rate in which the patients in the MI arm actually scheduled or attended their behavioral therapy appointments relative to the TAU arm.…”
Section: Discussionmentioning
confidence: 71%
“…This is superior to what we observed, especially in weeks 5–8. There are no clear estimates of how much adherence influences treatment outcome, but lower adherence is believed to undermine the efficacy of behavioral interventions (Gewirtz & Minen, 2019). A study of app‐based progressive muscle relaxation as a prophylactic treatment for migraine in adults found that highly adherent users (defined as two or more session per week) had a significantly greater reduction in headache frequency than users with low adherence (Minen et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…CBT-based mHealth apps have the potential to be used clinically to address a broader range of mental health conditions and are being investigated in clinical trials targeting conditions including postpartum depression, substance abuse, acrophobia, and migraine. [20][21][22][23] Preliminary data suggest there is no significant increase in adverse events with short-term use of CBT based digital therapeutics. As with other mHealth interventions further research is required to investigate whether successful clinical outcomes are sustainable long term.…”
Section: Digital Therapeuticsmentioning
confidence: 99%